Payroll Information System Design Using Waterfall Method - Matheus Supriyanto Rumetna; Tirsa Ninia Lina; Iriene Surya Rajagukguk; Frenny Silvia Pormes; Agustinus Budi Santoso (International Journal of Advances in Data and Information Systems, 2022)
The Sorong Islands District Office has problems in terms of employee payroll, because it is still carried out by means of recording using an employee job record book and tax deductions, etc. So it takes a very long time to record the salaries of employees according to class and position. This problem can be solved by utilizing ICT, which is to create a payroll information system according to class or position and the deductions evenly. The method used to design this payroll information system is the waterfall method, with Unified Modeling Language (UML), Macromedia Dreamweaver CS 6 for interface design and XAMPP for database design. The purpose of this research is to be able to process all employee salary data at the Sorong Kepulauan District office in detail so that it is effective and efficient in order to produce an information system that is fast, precise, and accurate.